Clinical Effects of a Natural Extract of Urinary Human Menopausal Gonadotrophin in Normogonadotropic Infertile Patients - Hua, Rui; Ma, Lan; Li, Hong (International Journal of Reproductive Medicine, 2013)
Purified human menopausal gonadotropin (HMG) is a natural product extracted from the urine of postmenopausal women that contains pituitary follicle-stimulating hormone (FSH), luteinizing hormone (LH), and a small amount of human chorionic gonadotropin (HCG). Here we retrospectively conducted a clinical pharmaceutical study on a cohort of normogonadotropic infertile patients addressed to long GnRH-agonist protocol with serum LH concentration ranging from 0.5 IU/L to 1.5 IU/L during the midfollicle phase, aiming at evaluating the effects of purified HMG supplementation during ovarian stimulation. There was no significant difference in either the basic clinical features of the patients or the pregnancy rate (71.4% versus 66.3%, P>0.05) or other related indicators of pregnancy outcome. However, there was a higher level of serum oestradiol (E2) on the day of human chorionic gonadotropin (HCG) (1999.10±860.50 IU/L versus 2883.29±1427.382 IU/L, P=0.000) but lower fertilization rate (89.1% versus 69.6%, P<0.000) in patients getting HMG supplementation and a higher risk of developing ovarian hyperstimulation syndrome (OHSS). We suppose that exogenous LH supplementation is not needed when serum LH concentration of the midfollicle phase is around 0.5–1.5 IU/L during the long GnRH-agonist protocol. Adding exogenous HMG may decrease the fertilization rate and increase the risk of developing OHSS.